The Influence of Behavior of SMEs on use of Accounting Information Systems in MSMEs - Ardin Doloksaribu; Audrey Margareth Siahaan; Melvin Sanro Jacobest Nainggolan (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
Micro, Small and Medium Enterprises (MSMEs) are business units managed by community groups and families. MSMEs have a strategic role in national economic development because they can also absorb many workers apart from contributing to national economic growth. The ability to provide and use accounting information is one of the areas for improvement on the management side. The population in this study are owners of small and medium businesses spread across the East Medan sub-district. According to the trade service and the Office of Cooperatives and Small and Medium Entrepreneurs in the East Medan sub-district, that is as many as 162 units. The sample in this study was 62 MSME owners. The sampling technique used was purposive sampling based on specific considerations or criteria. From the simple regression analysis test results, the behaviour of MSME actors has a positive effect on the use of accounting information systems. From the t-test results, the variable Behavior of MSME Actors is significant to the Use of Accounting Information Systems.Actor’s Behavior, SMEs, Accounting Information Systems